Forefoot strikers exhibit lower running-induced knee loading than rearfoot strikers - Kulmala, J.-P.; Avela, J.; Pasanen, K.; Parkkari, J. (Medicine & Science in Sports & Exercise, 2013)
Purpose: Knee pain and Achilles tendinopathies are the most common complaints among runners. The differences in the running mechanics may play an important role in the pathogenesis of lower limb overuse injuries. However, the effect of a runner`s foot strike pattern on the ankle and especially on the knee loading is poorly understood. The purpose of this study was to examine whether runners using a forefoot strike pattern exhibit a different lower limb loading profile than runners who use rearfoot strike pattern.